2015
DOI: 10.1111/cmi.12446
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of viral protein translation by indomethacin in vesicular stomatitis virus infection: role of eIF2α kinase PKR

Abstract: Indomethacin, a cyclooxygenase-1 and -2 inhibitor widely used in the clinic for its potent anti-inflammatory/analgesic properties, possesses antiviral activity against several viral pathogens; however, the mechanism of antiviral action remains elusive. We have recently shown that indomethacin activates the double-stranded RNA (dsRNA)-dependent protein kinase R (PKR) in human colon cancer cells. Because of the important role of PKR in the cellular defence response against viral infection, herein we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 41 publications
(93 reference statements)
1
40
0
1
Order By: Relevance
“…Our results show that indomethacin has potent, direct antiviral activity against the SARS CoV-2 (reduce the relative light unit to zero) in VERO E6 cells (Figure 1A), and does not show cytotoxicity to VERO E6 cells (Figure 1B). The current study, and reported by others, suggest that indomethacin has strong anti-Coronavirus activity in vitro 12,13 , including SARS COV-2, while aspirin does not. This suggests that indomethacin’s antiviral activity is not achieved by some mechanisms other than COX inhibition.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our results show that indomethacin has potent, direct antiviral activity against the SARS CoV-2 (reduce the relative light unit to zero) in VERO E6 cells (Figure 1A), and does not show cytotoxicity to VERO E6 cells (Figure 1B). The current study, and reported by others, suggest that indomethacin has strong anti-Coronavirus activity in vitro 12,13 , including SARS COV-2, while aspirin does not. This suggests that indomethacin’s antiviral activity is not achieved by some mechanisms other than COX inhibition.…”
Section: Discussionsupporting
confidence: 80%
“…Although the underlying mechanism requires further investigation, the results of indomethacin anti-SARS-CoV show that indomethacin does not affect virus infectivity, binding or entry into target cells, but acts early on the coronavirus replication cycle, selectively blocking viral RNA synthesis 12 . The only clear indomethacin antiviral mechanism is that, instead, triggers a cellular antiviral defense mechanism by rapidly and effectively activating PKR in an interferon- and dsRNA-independent manner 13 . PKR plays a critical role in the antiviral defense mechanism of the host, acting as a sensor of virus replication and 24 , upon activation, leading to eIF2α phosphorylation and block of protein synthesis in virally infected cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that indomethacin can increase the pH of lysosomes 31,32 . Moreover, some results suggest indomethacin can block viral RNA synthesis independently of the effect on cyclooxygenase inhibition and this effect was confirmed both in vitro and in vivo on canine coronavirus-infected dogs 33,34 .In conclusion, at this point, there are not enough studies to demystify the potential role of NSAIDs in COVID-19, however, in addition to standard anti-inflammatory and antipyretic properties other factors should be taken into account such as possible effect on the expression of ACE-2, interference with the autophagic flux and possible direct antiviral activity. We believe more attention should be directed towards these potential effects and structured clinical data should be collected in order to examine if some NSAIDs should be considered better than others for this indication.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaid)mentioning
confidence: 89%
“…Indomethacin (INDO), a cyclooxygenase-1/2 inhibitor, is routinely used in managing inflammation and pain in clinics [68,69]. INDO treatment of cells activates PKR in an interferon (IFN)-and dsRNA-independent manner, resulting in rapid (<5 min) phosphorylation of eIF2a [70] and termination of the viral translation in SARS-CoV-infected Vero cells with an IC 50 value of 50 mM [71]. INDO reduces the production of canine CoV in the canine adenocarcinoma A72 cells with an IC 50 value of 5 mM; 400 mM INDO can significantly reduce viral production (>1000-fold) in A72 cells (CC 50 > 550 mM), and oral administration of 1 mg/kg INDO daily for 4 days reduced production of canine CoV in dogs 1000-fold [71].…”
Section: Phosphorylation Of Eif2amentioning
confidence: 99%